Complicaciones de la cavidad oral en adultos mayores con diabetes mellitus tipo 2 - Colcha Llanga, Fernanda Liceth (2023)
ABSTRACT: Type 2 diabetes mellitus is considered a worldwide public health problem due to its high prevalence in the population. The aim of this study was to analyze oral complications in elderly people with DM2 diabetes through a bibliographic review of scientific articles published in scientific databases (Scielo, ProQuest, Google Scholar, Science Direct, PubMed, and others) in the last decade, thus obtaining 55 articles that met the requested parameters. At present, it is important to reinforce health education in this population so that future generations can reach old age knowing that the disease is preventable and that effective measures can be taken to improve the quality of life. The present literature review helps healthcare professionals to reduce the risk of chronic complications in these patients and to improve their quality of life to monitor, prevent, and controlling diabetes in terms of systemic and oral health status. The results determined that the most common oral cavity complications in older adults with type 2 diabetes mellitus are gingivitis, caries, oral mucosal alteration, xerostomia, taste alteration, burning mouth syndrome, oral candidiasis, mucormycosis or phycomycosis, rhomboid glossitis, lichen planus, and periodontal disease